Pelaksanaan Pembelajaran Tahfidz Al-Qur’an Oleh Guru Tunanetra Masa Pandemi COVID-19 di MAN 1 Surakarta - Nurul Maya Astuti (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: Implementation of Tahfidz Al-Qur'an Learning by Blind Teachers during the COVID-19 Pandemic at MAN 1 SurakartaThe purpose of this study was to find out 1) the implementation of tahfidz Al-Qur'an learning by blind teachers during the covid-2 pandemic 2) the efforts of blind teachers to create a conducive atmosphere during the implementation of tahfidz Al-Qur'an learning 3) The reasons for some class X students IPS 6 is less responsive to blind teachers during the implementation of tahfidz Al-Qur'an learning during the covid-19 pandemic. This research is a field research using a qualitative descriptive method. This research was conducted in May-June 2020 at MAN 1 Surakarta. The subjects in this study were tahfidz Al-Qur'an teachers (blind) and students of grade 10 Social Sciences 6. The informants were the head of the madrasa, the vice principal of the curriculum, tahfidz coordinator, and homeroom teacher of class 10 Social Sciences 6. The data collection technique was done by observation. , interviews, and documentation. In testing the validity of the data used triangulation techniques sources and methods. Data were analyzed by interactive analysis model. The results showed that first, the implementation of learning tahfidz Al-Qur'an by blind teachers during the covid-19 pandemic in class X IPS 6 students was online through the WhatsApp group, both using voice messages, text messages, and calls. Second, the efforts of blind teachers in creating a conducive atmosphere during the implementation of tahfidz Al-Qur'an learning in class X IPS 6 students are blind teachers giving punishment or punishment and giving rewards. Third, the reason that some of the actions of class X IPS 6 students are less responsive to blind teachers in the implementation of tahfidz Al-Qur'an learning are blind teachers who are less assertive and lack of parental supervision during online learning..